Body-mass index and risk of advanced chronic kidney disease: Prospective analyses from a primary care cohort of 1.4 million adults in England. - William G Herrington; Margaret Smith; Clare Bankhead; Kunihiro Matsushita; Sarah Stevens; Tim Holt; F D Richard Hobbs; Josef Coresh; Mark Woodward (PLoS ONE)
Background It is uncertain whether being overweight, but not obese, is associated with advanced chronic kidney disease (CKD) and how the size and shape of associations between body-mass index (BMI) and advanced CKD differs among different types of people. Methods We used Clinical Practice Research Datalink records (2000-2014) with linkage to English secondary care and mortality data to identify a prospective cohort with at least one BMI measure. Cox models adjusted for age, sex, smoking and social deprivation and subgroup analyses by diabetes, hypertension and prior cardiovascular disease assessed relationships between BMI and CKD stages 4-5 and end-stage renal disease (ESRD). Findings 1,405,016 adults aged 20-79 with mean BMI 27.4kg/m2 (SD 5.6) were followed for 7.5 years. Compared to a BMI of 20 to <25kg/m2, higher BMI was associated with a progressively increased risk of CKD stages 4-5 (hazard ratio 1.34, 95% CI 1.30-1.38 for BMI 25 to <30kg/m2; 1.94, 1.87-2.01 for BMI 30 to <35kg/m2; and 3.10, 2.95-3.25 for BMI ≥35kg/m2). The association between BMI and ESRD was shallower and reversed at low BMI. Current smoking, prior diabetes, hypertension or cardiovascular disease all increased risk of CKD, but the relative strength and shape of BMI-CKD associations, which were generally log-linear above a BMI of 25kg/m2, were similar among those with and without these risk factors. There was direct evidence that being overweight was associated with increased risk of CKD stages 4-5 in these subgroups. Assuming causality, since 2000 an estimated 39% (36-42%) of advanced CKD in women and 26% (22-30%) in men aged 40-79 resulted from being overweight or obese. Conclusions This study provides direct evidence that being overweight increases risk of advanced CKD, that being obese substantially increases such risk, and that this remains true for those with and without diabetes, hypertension or cardiovascular disease. Strategies to reduce weight among those who are overweight, as well as those who are obese may reduce CKD risk, with each unit reduction in BMI yielding similar relative reductions in risk.